THE RELATIONSHIP BETWEEN INDIAN OCEAN HIGH PRESSURE AND RUNOFF VARIABILITY IN THE DONNELLY RIVER CATCHMENT IN SOUTHWEST WESTERN AUSTRALIA: A CASE STUDY - Rehman, S. U.; Iqbal, M. J. (The Nucleus, 2011)
This paper investigates the relationship between changes in the Indian Ocean High Pressure and the runoff variability in Donnelly river catchment of Southwest Western Australia (SWWA). Significant outcomes suggests that the intensity as well as the Zonal movement of Indian ocean high pressure significantly influence on winter stream flow. When Indian ocean high pressure shifted towards West, stream flow in Donnelly river increases, and vice versa. The multiple correlation between stream flow and Indian Ocean High Pressure (IOHP & IOHLN) is 0.48, while correlation between Southern Oscillation Index (SOI) is 0.40. Centers of Action (COA) indices explains 21% stream flow variability while Southern Oscillation Index (SOI) explains only 15% stream flow variability.